Bridge to Bigpush or Backwash? : Market Integration, Reallocation, and Productivity Effects of Jamuna Bridge in Bangladesh - Blankespoor, Brian; Emran, M. Shahe; Shilpi, Forhad J.; Xu, Lu (World Bank, Washington, DC, 2018)
This paper uses a quasi-experimental study of a major bridge construction in Bangladesh to understand the effects of a large reduction in trade costs on the pattern of structural change and agricultural productivity. The paper develops a spatial general equilibrium model with a core and two hinterlands at the opposite sides separated by rivers, and allows for productivity gains through agglomeration in the agriculture and manufacturing sectors. The model yields insights different from the standard core-periphery and trade models: (i) the newly connected hinterland may experience higher population density and agricultural productivity despite significant de-industrialization; (ii) even with increased specialization in agriculture, the share of agricultural employment may decline when interregional trade requires local services (such as processing and trading); and (iii) the strongest effects on employment structure are felt not necessarily in the areas next to the bridge but in the areas that move out of autarky as a result of the bridge. The empirical estimation uses doubly robust estimators in a difference-in-difference design where the comparison hinterland comes from a region which was supposed to be connected to the core (capital city) by the proposed, but not yet constructed, Padma bridge. In the short run, there is significant labor reallocation from agriculture to services in the connected hinterland, but no perceptible effects on the employment share of manufacturing, population density, and night-lights. In the long run, the labor share of manufacturing declines in the treatment hinterland and increases in the core. However, there are significant positive effects on population density, night light luminosity, and agricultural yields in the treatment hinterland which contradict backwash effects of the bridge. The effects of the bridge on intersectoral labor allocation are spatially heterogeneous, with relatively weak effects in the areas close to the bridge.